Narrations on Digital Unconsciousness: A Psychoanalytical Perspective on SCPs - Francesca De Marino (Humanities, 2023)
With a psychoanalytic lens, this article will examine some forms of contemporary narration, which develop in the virtual world and appear as phenomena related to mythopoiesis in preadolescence. Such forms put the body at the heart of the identity transformation. The body becomes a staple of the metamorphosis of suffering and drives the elaboration of pain. While always on the edge of ambiguity, these stories nurture persecution, fear, a state of permanent and ruleless alert, and a flood of primordial affects questioning the boundaries between the organic and the inorganic, which is a problem that the common sense of our time seems to feel with greater urgency.